Analysis and Evaluation of Safety Culture Performance in Drilling Activities at PT XYZ Upper Mile Gas South Sumatera Through Implementation of Occupational Safety Observation (PEKA) - Willem KOMPERI; Edi SETIAWAN; Sugiarto SUGIARTO (International Journal of Environmental, Sustainability, and Social Science, 2025)
PT XYZ as one of the drilling companies engaged in the upstream oil and gas industry has developed a PEKA (Occupational Safety Observation) system which is used to monitor the risk of work accidents. This study aims to analyze the performance of safety culture in drilling activities at PT XYZ through the level of PEKA implementation using multiple linear regression analysis. The results of this study indicate that unsafe conditions are more dominant than unsafe actions at PT. XYZ in the period 2022 to 2024. The anomaly of unsafe actions compared to unsafe conditions at PT. XYZ is suspected to be due to biased observations or reporting. However, in general, the performance of safety culture in drilling activities at PT. XYZ upstream oil and gas in South Sumatra as measured through the implementation of PEKA has been running quite well. This is indicated by the results of multiple linear regression analysis which are significant simultaneously and partially and the level of safety culture of each variable which is at the pro-active level.